Extraction of Pandanus Amaryllifolius essential oil from pandan leaves - Nur Syazwani, Ghazali (2011)
The extraction process is the key operation for obtaining oils. The oils are extracted by chemical method where strong acids are used. The process using solvent extraction has been used for extraction of pandan leaves. In this experiment, there are four types of solvent will be used which is ethyl acetate, hexane,chloroform, and, methanol. The pandan leaves was sliced into small size before added before being put in a beaker containing two solvents and then the solution will be unstable for 2 4 and 6 hours. The effectiveness of different ratio of solvent process will be studied. The composition of the essential oils extracted by solvent from leaves parts of pandan (Pandanus amaryllifolius) were analyzed by using gas chromatography (GC-MS). The major component in Pandanus amaryllifolius was 2-acetyl-l-pyrroline but in present study only the minor component was obtained which were 3-Hexanol and 3-Hexanone. Significantly the result shows that the solvent ratio chloroform: ethyl acetate get a large amount of oils.